2013
DOI: 10.1177/0004865813485590
|View full text |Cite
|
Sign up to set email alerts
|

Pre-recording testimony in New Zealand: Lawyers’ and victim advisors’ experiences in nine cases

Abstract: This paper reports on lawyers’ and victim advisors’ experiences with nine pre-recorded hearings involving young people as witnesses in criminal court cases in Auckland. Focus groups, interviews and a questionnaire were used to elicit perceived advantages and disadvantages, issues in the preparation for hearings, conducting the hearings and showing the pre-recordings at trial. Although the sample is not large enough to generate definitive conclusions, 21 of 24 participants described pre-recorded hearings positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…The evidential value of forensic interviews will vary across jurisdictions depending on their legal requirements. In some countries and jurisdictions, the recording of the interview may be admissible in court and serve as the child’s evidence-in-chief, e.g., because special measures for vulnerable witnesses are enacted in legislation (e.g., Davies & Hanna, 2013; Hanna, Davies, Crothers, & Henderson, 2012; Melinder, Burrell, Eriksen, Magnussen, & Wessel, 2016; Westera, Powell, Goodman-Delahunty, & Zajac, 2020), or because it meets the requirements of one or more exceptions to the rule against hearsay (e.g., in the United States). We do not review or discuss the legislation surrounding the admissibility of video-recorded interviews as evidence-in-chief, nor any special arrangements that might be needed to facilitate this.…”
mentioning
confidence: 99%
“…The evidential value of forensic interviews will vary across jurisdictions depending on their legal requirements. In some countries and jurisdictions, the recording of the interview may be admissible in court and serve as the child’s evidence-in-chief, e.g., because special measures for vulnerable witnesses are enacted in legislation (e.g., Davies & Hanna, 2013; Hanna, Davies, Crothers, & Henderson, 2012; Melinder, Burrell, Eriksen, Magnussen, & Wessel, 2016; Westera, Powell, Goodman-Delahunty, & Zajac, 2020), or because it meets the requirements of one or more exceptions to the rule against hearsay (e.g., in the United States). We do not review or discuss the legislation surrounding the admissibility of video-recorded interviews as evidence-in-chief, nor any special arrangements that might be needed to facilitate this.…”
mentioning
confidence: 99%
“…However, two appeals (MvR (CA 335/ 2011) and RvE (CA 339/2011)) in relation to the pre-recording of cross-examination in 2011 determined that pre-recording should be restricted to special, and by implication, rare circumstances. Lawyers' and victim advisors' experiences of the nine cases in which the entire testimony had been pre-recorded were largely positive (Davies & Hanna, 2013), and professionals interviewed in relation to the introduction of the Whangarei Young Witness Pilot Protocol raised this as a solution to the problem of pre-trial delay (Randell, 2017;Randell et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This usually takes place in front of a jury, although in CSA cases complainants are typically cross-examined via CCTV (ALRC, 2010;Cossins, 2009). Research has shown this measure has numerous benefits, including a reduction in the stress and trauma that complainants experience in court (Eastwood & Patton, 2002;Hamlyn et al, 2004), preserving evidence by recording the complainants' accounts closer to the time of the abusive incidents (E. Davies & Hanna, 2013;Hanna, Davies, Henderson, Crothers, & Rotherham, 2010), and reducing the need for complainants to tell their story numerous times TRIAL DISCUSSIONS OF CHILD WITNESS INTERVIEWS (La Rooy, Lamb, & Pipe, 2009). Pre-recorded evidence also allows prosecutors and defence to better prepare their cases (Burrows & Powell, 2014b;Cashmore & Trimboli, 2005), and enables the court to edit out inadmissible evidence and thus reduce the chance of a mistrial (E. Davies & Hanna, 2013;Hanna et al, 2010).…”
mentioning
confidence: 99%
“…Despite these many advantages of pre-recorded child witness interviews, issues remain with their use in court. First and foremost, the quality of the interview (and evidence) is dependent on the skills of the interviewer (E. Davies & Hanna, 2013;Lamb, 2016), and studies have shown that the quality of interviews is often poor. For example, legal professionals (including both prosecutors and defence lawyers) have expressed concerns that interviews are frequently too long and include irrelevant and excessive detail (Cashmore & Trimboli, 2005;McConachy, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation